A Low Power Frequency Synthesizer Design for Wireless Power Transfer Applications - AlSuwaidi, Maryam Rashed Obaid (2023)
A Master of Science thesis in Electrical Engineering by Maryam Rashed Obaid AlSuwaidi entitled, “A Low Power Frequency Synthesizer Design for Wireless Power Transfer Applications”, submitted in April 2023. Thesis advisor is Dr. Lutfi Albasha and thesis co-advisor is Dr. Hasan Mir. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).